2007
DOI: 10.1002/eat.20433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social comparisons with peers on women's body satisfaction and exercise behavior

Abstract: Incidental comparisons with fit versus unfit peers can affect women's body satisfaction and fitness-related behavior in a naturalistic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…Results indicated that there was no significant difference between the conditions on body satisfaction. Although previous research has not found differences in body satisfaction following the opportunity to make downward comparisons, it has been suggested that failure to observe this may have been due to the use of overweight rather than obese comparators (Lin & Kulik, 2002;Wasilenko et al, 2007). Comparators in the present study were obese, however, no difference was found on body satisfaction between the two conditions.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Results indicated that there was no significant difference between the conditions on body satisfaction. Although previous research has not found differences in body satisfaction following the opportunity to make downward comparisons, it has been suggested that failure to observe this may have been due to the use of overweight rather than obese comparators (Lin & Kulik, 2002;Wasilenko et al, 2007). Comparators in the present study were obese, however, no difference was found on body satisfaction between the two conditions.…”
Section: Discussioncontrasting
confidence: 78%
“…However, research suggests that body satisfaction is not positively influenced by downward social comparisons (e.g., Lin & Kulik, 2002;Wasilenko et al, 2007). For mood, the evidence is mixed.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such an influence could come not only from information, but also to the exposure to the behaviour of peers. Wasilenko, Kulik, and Wanic (2007) found peer exposure can influence women's Body Dissatisfaction and exercise duration. Gravener, Haedt, Heatherton, and Keel (2008) showed that there were significant associations between perceived peer dieting and diet in women and men.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of examining this question becomes more important due to the fact that many gyms provide clients with televisions to watch during exercise and people are likely to watch the television when exercising at home. Previous research by Wasilenko et al (2007) found exposure to a fit peer in a campus gym caused undergraduate females to have greater body dissatisfaction and exercise for shorter duration than when exposed to an unfit peer or no peer. Therefore, to avoid circumstances like this, it would make sense for women to seek out opportunities to exercise individually without chances of social comparison or with a similar appearance cohort group which may attenuate social comparison.…”
mentioning
confidence: 98%